2001
DOI: 10.1053/gast.2001.25478
|View full text |Cite
|
Sign up to set email alerts
|

Growth Retardation, Duodenal Lesions, and Aberrant Ileum Architecture in Triple Null Mice Lacking EGF, Amphiregulin, and TGF-α

Abstract: EGF-R ligands are required for development and mucosal maintenance in mouse small intestine. Both maternal and neonatal sources of growth factors are required for optimal pup growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 37 publications
2
69
0
Order By: Relevance
“…Mice lacking EGF, TGF-α or amphiregulin fail to recapitulate the full range of EGFR-knockout phenotypes. EGF-and amphiregulin-null mice do not have an easily identifiable phenotype [131,132]. Targeted and naturally occurring (waved-1) mutations of TGF-α in mice leads to defects in hair follicle and eye development, phenotypes similar to the spontaneous EGFR mutation of the waved-2 mouse [133][134][135].…”
Section: Erbb Members In Mammalian Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice lacking EGF, TGF-α or amphiregulin fail to recapitulate the full range of EGFR-knockout phenotypes. EGF-and amphiregulin-null mice do not have an easily identifiable phenotype [131,132]. Targeted and naturally occurring (waved-1) mutations of TGF-α in mice leads to defects in hair follicle and eye development, phenotypes similar to the spontaneous EGFR mutation of the waved-2 mouse [133][134][135].…”
Section: Erbb Members In Mammalian Developmentmentioning
confidence: 99%
“…Female mice with combined deficiency of amphiregulin, EGF and TGF-α display diminished mammary gland ductal outgrowth during puberty with severe defects in mammopoeisis and lactogenesis [131]. Triple mutant mice deficient in EGF, TGF-α, and amphiregulin partially phenocopy EGFR-deficient mice, displaying decreased cell proliferation in the intestine leading to attenuated ileal villi and decreased mucin production [132].…”
Section: Erbb Members In Mammalian Developmentmentioning
confidence: 99%
“…EGFR can be activated by several ligands, including epidermal growth factor (EGF), transforming growth factor (TGF)-α, heparin-binding EGF (HBEGF), betacellulin (Btc), amphiregulin (AREG), and epiregulin (EREG). Although mice lacking TGF-α, EGF, or AREG individually do not show any gastrointestinal phenotype, triple null mice lacking EGF, AREG, and TGF-α show duodenal lesions and aberrant ileum architecture (16). Moreover, mice lacking TGF-α or EREG or EGFR kinase-defective Waved-2 mice are highly susceptible to chemically induced colitis using DSS (14,15,17).…”
mentioning
confidence: 99%
“…Gene targeting experiments have demonstrated that mice null for EGF, AR (Luetteke et al, 1999), or TGF-alpha (Mann et al, 1993) are fertile. In addition, compound knockouts for all three alleles are still fertile (Troyer et al, 2001).…”
Section: Epidermal Growth Factormentioning
confidence: 99%